Electrochemical Activated Nitrogen‐doped Carbon as Highly Efficient Electrocatalysts for Hydrogen Evolution Reactions. Issue 7 (20th June 2022) - Liang, Cheng‐lu; Ye, Ni‐ni; Li, Jia‐li; Li, Xing‐qiu; Lei, Shuai; Huang, Yuan‐peng; Wu, Jing‐jie; Liu, Yang; Yang, Wei
Abstract: Nitrogen‐doped carbon materials play an important role in the electrolysis of water due to their low cost and high stability. The major roles of N‐doped carbon materials in water electrolysis are electrocatalysts or catalyst support for metal‐based catalysts. However, the evolution of structures and performances of N‐doped carbon catalysts/support during electrochemical hydrogen evolution reactions (HER) process has been seldom reported. Here, we found that the catalytic activities of N‐doped carbon were electrochemically activated during the in‐situ HER process. After electrochemical activation, the catalytic activities of the nitrogen‐doped carbon towards HER were drastically improved and even approached the state‐of‐the‐art Pt/C catalyst. The examination of activation conditions and correlation with the catalytical performances demonstrated that the emerged pyridine N‐oxide structure was responsible for the enhanced catalytic performances. The reconstruction of surface chemical structures near the active sites during activation results in the enhanced surface hydrophilicity, which in turn makes the active sites more accessible by the protons. As a result, the catalytic HER performances were drastically improved in the activated catalysts. Abstract : The electrocatalytic HER performances of nitrogen‐doped carbon were drastically improved via electrochemical activation, which induced the C−N breaking and reconstruction. The reconstructed pyridinic N−O unit makes the pyridinic N active sites more accessible by the protons via enhanced surface hydrophilicity. As a result, the catalytic HER performances were drastically improved in the activated catalysts.